2013
DOI: 10.1080/09650792.2013.789717
|View full text |Cite
|
Sign up to set email alerts
|

Teacher professional development through collaborative action research: impact on foreign English-language teaching and learning

Abstract: In 2011, we, a group of English as a foreign language teachers at a secondary school in Argentina, decided to investigate our teaching practices through collaborative action research so as to improve our students' learning opportunities and thus revitalise English Language Teaching in our context. We implemented and evaluated the integration of content and language learning in our classrooms through the development of our own materials. The experience revealed a growth in professional development and how our m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 37 publications
1
49
0
Order By: Relevance
“…Teacher research can encompass action research (Burns, 2010;Dikilitaş & Griffiths, 2017) and exploratory practice (Allwright & Hanks, 2009;Hanks, 2017) and it is used as continuing professional development in Latin American countries such as Argentina (Banegas, Pavese, Velázquez, & Vélez, 2013), Brazil (Seixas Vial & Kurtz de Souza Welp, 2015, Chile (Burns, Westmacott, & Hidalgo Ferrer, 2016;Smith, Connelly, & Rebolledo, 2014), Mexico (Roux & Mendoza Valladares, 2014) and in other countries, for example Australia (Edwards & Burns, 2016b), China (Wang & Zhang, 2014;Yuan et al, 2016), or Turkey (Wyatt & Dikilitaş, 2015). Previous research reports how future teachers (Villacañas de Castro, 2014) and practising teachers engage in action research to bridge the so-called gap between theory and practice and produce context-responsive answers to their classroom concerns (Edwards & Burns, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Teacher research can encompass action research (Burns, 2010;Dikilitaş & Griffiths, 2017) and exploratory practice (Allwright & Hanks, 2009;Hanks, 2017) and it is used as continuing professional development in Latin American countries such as Argentina (Banegas, Pavese, Velázquez, & Vélez, 2013), Brazil (Seixas Vial & Kurtz de Souza Welp, 2015, Chile (Burns, Westmacott, & Hidalgo Ferrer, 2016;Smith, Connelly, & Rebolledo, 2014), Mexico (Roux & Mendoza Valladares, 2014) and in other countries, for example Australia (Edwards & Burns, 2016b), China (Wang & Zhang, 2014;Yuan et al, 2016), or Turkey (Wyatt & Dikilitaş, 2015). Previous research reports how future teachers (Villacañas de Castro, 2014) and practising teachers engage in action research to bridge the so-called gap between theory and practice and produce context-responsive answers to their classroom concerns (Edwards & Burns, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This finding has a grain of similarity with that of a group of EFL teachers at a secondary school in Argentina who investigated their teaching practices through collaborative action research. The group has found that action research Downloaded by [University of Nebraska, Lincoln] at 23:51 07 June 2016 has a motivational value driving them (the investigators) to develop (professionally) and to build identity mainly characterized by the ability to introduce changes in the curriculum through informed and democratic decisions that were truly context responsive, the cumulative effect of which positively impacted their learners' motivation to learn the English language which is the basis for learning communicative skills and subject contents (Banegas et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This underpins the two issues that MacBeath et al (2003, 5) mentioned as the benefits of consulting pupils: 'feeling that you are respected and that you are listened to and taken seriously', and 'knowing that your views are having an impact on how things are done in school and classroom'. The role of action research in fostering student motivation is also supported by Banegas et al (2013), who conducted collaborative action research to improve EFL students' learning opportunities in Argentina. They revealed that collecting feedback from students regarding the quality of their learning and reflecting on classroom problems had a positive impact on teacher professional development and student motivation to learn English.…”
Section: Research Question 3: Students' Feelings About Being Involvedmentioning
confidence: 98%